Anmeldelser - Lewis Hammond, Susan (Danish Yearbook of Musicology, 2004)
Review of: Ludwig Senfl, Motetter / Motetten / Motets, ed. Ole Kongsted. (Capella Hafniensis Editions Serie A: Renaissancemusik, 1). København: Capella Hafniensis Editions in cooperation with The Royal Library, 2001. Johannes Flamingus, Opusculum cantionum, 1571, ed. Ole Kongsted. (Capella Hafniensis Editions Serie A: Renaissancemusik, 2). København: Capella Hafniensis Editions in cooperation with The Royal Library, 2002.